2022
DOI: 10.3390/microorganisms10071258
|View full text |Cite
|
Sign up to set email alerts
|

Is SARS-CoV-2 Directly Responsible for Cardiac Injury? Clinical Aspects and Postmortem Histopathologic and Immunohistochemical Analysis

Abstract: Myocardial injury in patients with SARS-CoV-2 infection may be attributed to the presence of the virus at the cellular level, however, it may also be secondary to other diseases, playing an essential role in the evolution of the disease. We evaluated 16 patients who died because of SARS-CoV-2 infection and analyzed the group from both clinical and pathological points of view. All autopsies were conducted in the Sibiu County morgue, taking into consideration all the national protocols for COVID-19 patients. Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Changes in nuclei, as well as syncytium formation, were rarely observed. Regarding nuclear changes, Oprinca et al 49 observed nuclear pyknosis in cardiomyocytes in four fatal cases of COVID-19. A placenta study showed that SARS-CoV-2 infection induces, in addition to other changes, karyorrhexis in the syncytiotrophoblast.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in nuclei, as well as syncytium formation, were rarely observed. Regarding nuclear changes, Oprinca et al 49 observed nuclear pyknosis in cardiomyocytes in four fatal cases of COVID-19. A placenta study showed that SARS-CoV-2 infection induces, in addition to other changes, karyorrhexis in the syncytiotrophoblast.…”
Section: Discussionmentioning
confidence: 99%
“…For the chromogenic immunohistochemical reaction, we employed an anti-mouse HRP IgG secondary antibody with DAB chromogen. Hematoxylin was used for counterstaining [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Hematoxylin served as the counterstain. The immunohistochemical preparation adhered to the same protocol as previous research conducted in our laboratory [ 32 ]. For the positive controls, we acquired Hydrophilic Plus slides containing SARS-CoV-2 positive lung tissues ( Figure 4 ).…”
Section: Methodsmentioning
confidence: 99%